ANALISA PENGARUH SERVICE QUALITY DAN PRICE PERCEPTION TERHADAP CUSTOMER SATISFACTION DENGAN PERCEIVED VALUE SEBAGAI VARIABEL INTERVENING PADA COFFEE TOFFEE JATIM EXPO SURABAYA - retnaningsih, wiwik; perdana siahan, batara hotma (JEM17: Jurnal Ekonomi Manajemen, 2017)
AbstractCoffee Toffee can be used for meetings or other events. In terms of service Coffee Toffee has an excellent barista and knowledgeable about coffee, cozy atmosphere equipped with various facilities, making Coffee Toffee as a place for those who want to refresh the mind while relaxing and enjoy a cup of cappucino, latte or espresso. This study aims to analyze the effect of service quality and price perception to customer satisfaction with perceived value as intervening variable at Coffee Toffee Jatim ExpoThis research belongs to the type of causal research. The population used is Coffee Toffee East Java Expo Surabaya customers who have purchased Service Quality from Coffee Toffee Jatim Expo Surabaya, while the sample used in this research is 120 people taken by using purposive sampling sampling technique. Data collection was done by distributing questionnaires. Data analysis technique used is Structural Equation Modeling (SEM) with AMOS software.The results in this study indicate that (1) there is influence but not significant from service quality from Coffee Toffee Java Expo Surabaya to perceived value; (2) there is influence but not significant from service quality from Coffee Toffee Jatim Expo Surabaya to customer satisfaction; (3) there is influence Price Perception from Coffee Toffee Jatim Expo Surabaya to perceived value; (4) there is influence of price perception from Coffee Toffee Jatim Expo Surabaya to customer satisfaction; and (5) there is influence perceived value from Coffee Toffee Jatim Expo Surabaya to customer satisfaction.Â Kata kunci: service quality, price perception, perceived value, customer satisfaction